2014
DOI: 10.1038/sc.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological prophylaxis for deep vein thrombosis in acute spinal cord injury: an Indian perspective

Abstract: Study design: Prospective randomized single blind study. Objectives: To find out the incidence of deep vein thrombosis (DVT) in Indian acute spinal cord injury (ASCI) subjects with and without pharmacological prophylaxis. Setting: Indian Spinal Injuries Centre. Methods: Seventy four ASCI subjects were randomly divided into two groups with 37 subjects each: group I received no antithrombotic prophylaxis, and only physical measures like compression stockings were employed for prophylaxis, whereas group II receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…4,[12][13][14] Institutional transfers Studies have also established the importance of minimizing institutional transfers before reaching the definitive institution in achieving an optimal outcome. 15 Our study revealed that this was far from optimal in the ASCoN region. Sixty-three percent of the patients reported that they reached a definitive institution after two or more institutional transfers.…”
Section: Pre-hospital Carementioning
confidence: 73%
“…4,[12][13][14] Institutional transfers Studies have also established the importance of minimizing institutional transfers before reaching the definitive institution in achieving an optimal outcome. 15 Our study revealed that this was far from optimal in the ASCoN region. Sixty-three percent of the patients reported that they reached a definitive institution after two or more institutional transfers.…”
Section: Pre-hospital Carementioning
confidence: 73%
“…They found DVT in 47% of the placebo group, 50% of the LDUH group, and 7% of the group that received the combination of FNS and LDUH (p < 0.05). Halim et al reported DVT in 22% of thirty-seven SCI patients given GCSs and in 5% of thirty-seven patients who received enoxaparin 40 mg once daily plus GCSs (Halim, 2014).…”
Section: Anticoagulant Methods Of Thromboprophylaxismentioning
confidence: 99%
“…However, an age effect was not observed in large study of more than 12,000 SCI patients from California (Godat, 2015). ■ Complete versus incomplete injuries: The risks of VTE are greater with motor complete (AIS A) compared with incomplete (AIS B, C, or D) injuries (Aito, 2003;Halim, 2014;Matsumoto, 2015). ■ Concomitant lower-extremity fractures:…”
Section: Funding and Potential Conflicts Of Interestmentioning
confidence: 99%
See 2 more Smart Citations